An introduction to optical emission spectroscopy and laser-aided spectroscopy techniques for low-temperature plasma analyses - Nafarizal, Nayan; Rahmat, Sanudin; Tengku Nadzlin, Tengku Ibrahim (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.